2004
DOI: 10.1002/mrm.20114
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI of the rodent somatosensory pathway using multislice echo planar imaging

Abstract: A multislice EPI sequence was used to obtain functional MR images of the entire rat brain with BOLD contrast at 11.7 T. Ten to 11 slices covering the rat brain, with an in-plane resolution of 300 m, provided enough sensitivity to detect activation in brain regions known to be involved in the somatosensory pathway during stimulation of the forelimbs. These regions were identified by warping a digitized rat brain atlas to each set of images. Data analysis was constrained to four major areas of the somatosensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
108
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(123 citation statements)
references
References 41 publications
13
108
2
Order By: Relevance
“…On the other hand, studies conducted by using the spin-echo EPI sequence (Huttunen et al, 2008;Keilholz et al, 2004) showed that the BOLD signal measured at 4.7 and 11.7 T peaked at 3 Hz during the forepaw stimulation (30 to 45-s duration). These results and ours using the spin-echo sequence contradict those using the gradient-echo sequence (Gyngell et al, 1996;Brinker et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…On the other hand, studies conducted by using the spin-echo EPI sequence (Huttunen et al, 2008;Keilholz et al, 2004) showed that the BOLD signal measured at 4.7 and 11.7 T peaked at 3 Hz during the forepaw stimulation (30 to 45-s duration). These results and ours using the spin-echo sequence contradict those using the gradient-echo sequence (Gyngell et al, 1996;Brinker et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…A large number of studies have been conducted by using electrical stimulations on the rat somatosensory model by using the blood oxygenation level-dependent (BOLD) fMRI (Brinker et al, 1999;Gyngell et al, 1996;Huttunen et al, 2008;Keilholz et al, 2004;Kida et al, 2001;Ogawa et al, 2000;Van Camp et al, 2006), laser Doppler flowmetry (LDF) (Ances et al, 1999;Detre et al, 1998;Matsuura and Kanno, 2001;Ngai et al, 1999;Ureshi et al, 2004), and optical imaging (Sheth et al, 2004;. Since BOLD signals correlate with the deoxygenated hemoglobin content (Ogawa et al, 1990), the stimulus frequency dependence of BOLD signals should correspond to the deoxygenated hemoglobin content assessed by optical imaging, and a similar dependence is expected with regard to changes in the cerebral blood flow (CBF) (Hoge et al, 1999;Kida et al, 2000;Silva et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a number of studies have optimized stimulation protocols for the model of electrical somatosensory stimulation of a rat paw. Typically, the amplitude, repetition rate of short current pulses and the duration of the train of pulses have been varied (Leniger-Follert and Hossman, 1979;Gyndell et al, 1996;Brinker et al, 1999;Silva et al, 1999;Ogawa et al, 2000;Keilholz et al, 2004). Using this paradigm, short pulses of a few hundred microseconds of a few mAmp current and repetition rates of 3-5 Hz elicit the maximum evoked SEP and fMRI responses.…”
Section: Introductionmentioning
confidence: 99%
“…Using this paradigm, short pulses of a few hundred microseconds of a few mAmp current and repetition rates of 3-5 Hz elicit the maximum evoked SEP and fMRI responses. The low repetition rates that maximize the response of the paw somatosensory cortex are assumed to be due to refractory phenomena, when a stimulus reduces the response to the subsequent stimulus, and a train of activations occurring at too high a repetition rate cannot sustain maximum effects (Brinker et al, 1999;Ogawa et al, 2000;Keilholz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%